2020
DOI: 10.1108/jaee-02-2019-0053
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing liquidity position of Indian manufacturing companies

Abstract: PurposeThe purpose of this paper is to investigate the increasing demand for corporate liquidity and examines the various factors influencing the cash position of firms in India. The financial policy to hold cash gained impetus after the financial crisis when the companies faced a severe cash crunch. However, the firms operating in emerging nations have an imperfect market mechanism with stringent regulatory norms. Thus, this paper a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Liquidity is found to be highly significant and has a positive impact on firm value with coefficients 0.28, 0.33 and 0.23, respectively. The positive findings of liquidity and firm value are also suggested in studies by Rani et al (2019) and Tripathy and Uzma (2020).…”
Section: Gmm Estimation Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Liquidity is found to be highly significant and has a positive impact on firm value with coefficients 0.28, 0.33 and 0.23, respectively. The positive findings of liquidity and firm value are also suggested in studies by Rani et al (2019) and Tripathy and Uzma (2020).…”
Section: Gmm Estimation Resultssupporting
confidence: 60%
“…Thus higher liquidity ratio indicates that firms can manager a higher percentage of the current liabilities through current assets. Liquidity is a measure of the ability of a firm to meet its obligations and has a positive linkage with firm value (Rani et al , 2019; Tripathy and Uzma, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…India saw its financial accounting standards for the domestic companies converge with International Financial Reporting Standards through Ind AS (Indian Accounting Standards applicable from FY 2016–2017) and the implementation of the goods and services tax from 2017. As per Tripathy and Uzma (2020), India was seen as an attractive destination for foreign investments amongst emerging markets because of its resilience and potential to tide the Asian financial crisis through rapid development, as well as its manufacturing focus. Therefore, India was chosen as the setting for this study and the individual accountant was the unit of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, India was chosen as the setting for this study and the individual accountant was the unit of analysis. Furthermore, Tripathy and Uzma (2020) also observed that the behaviour of Indian manufacturing firms (which would employ accountants) was different from their international peers in many operational areas such as cash holding, which suggests that the findings of the studies undertaken in developed economies may or may not be relevant for emerging markets.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the people who purchase those shares are mentioned as shareholders of that company; with respect to this situation, those shareholders have partial ownership of that company and receive an ownership interest in that company. A company can meet its liquidity requirements by borrowing funds from the business; in other words, the liquidity needs of a business are met with equity financing (Tripathy and Uzma, (2020)).…”
Section: Introductionmentioning
confidence: 99%